Article Length and Citation Outcomes - Syed Hasan; Robert Breunig (Institute of Labor Economics (IZA), 2020)
We examine whether there is any causal effect of article length on citation. Focusing on articles published between 2010 and 2014 in the top five journals in economics and their citation count in Google Scholar, we find that a one per cent increase in page length generates a 0.55 per cent increase in the number of citations. A small survey of economists suggests that this effect may be a result of longer articles containing both theory and empirical elements. We interpret our result as a causal estimate conditional on average quality per page.
Keywords: A14; 330; article length; Google Scholar; citations; economics